SEJARAH KODIFIKASI HUKUM ISLAM DAN PENGEMBANGAN TEORI HUKUM MODERN - Achmad Musyahid (Fakultas Syariah dan Hukum Islam Institut Agama Islam Negeri (IAIN) Parepare, 2012)
This article describes the issue of codification of Islamic law in the development of modern legal theory. From the assessment results obtained by understanding some of the literature that was essentially the codification of Islamic law is the codification of the rules of fiqh and usul fiqh rules and the development of theories of Islamic law that is based on Islamic law epistimologi. Therefore, the pattern includes the codification of Islamic law; codification of the rules of fiqh which includes three phases, namely the development of a period of growth and formation, the development and codification and the maturity and refinement. While codification of usul al-fiqh includes not only the rules of jurisprudence but also related to the struggle of who the originator of usul al-fiqh as a mode of philosophical thought in epistimologi Islamic law. Birth of legal theories under Islamic law epistimologi Why refer to the style of traditional and rational thinking in Islamic law underlies epistimologi birth maqasid al-Shari'ah theory developed by Islamic jurists before the era and the era of al-Syātibi maqashid theory after al- Syātibi.